Productivity and profitability of rapeseed (Brassica rapa var. dichotoma) under system of rapeseed intensification (Journal of Oilseed Brassica, 2026)
A field experiment was conducted during rabi 2016-2017 and 2017-18 at Assam Agricultural University, Jorhat to find out the optimum irrigation scheduling and to evaluate the suitable planting geometry of rapeseed (Brassica rapa var. dichotoma) under system of rapeseed intensification with 4 irrigation regimes viz. one irrigation at flower initiation stage, two irrigations at flower initiation and 50% flowering stage, three irrigations at flower initiation, 50% flowering and at siliqua development stage and rainfed with four different planting geometry viz. 30 cm × 30 cm, 30 cm × 25 cm, 25 cm × 25 cm and 30 cm × 5-7 cm. Three irrigations applied at flower initiation, 50% flowering and at siliqua development stage recorded the highest growth viz., plant height, dry matter/m2, primary branches/plant and crop growth rate and yield attributes viz., number of branches/ plant, siliquae/plant and number of seeds/ siliqua. Three irrigations applied at flower initiation, 50% flowering and at siliqua development stage recorded highest seed and stover yield, net return and field water use efficiency. Among the planting geometry, 30 cm × 30 cm recorded the highest plant height, total branches/ plant and siliqua/ plant. However, planting geometry 25 cm × 25 cm recorded the highest seed yield, net return and water use efficiency.